Determination the validity of the new developed Sport Experts® hand grip dynamometer, measuring continuity of force, and comparison with current Takei and Baseline® dynamometers - Güclüöver, A.; Kutlu, M.; Cigerci, A. E.; Esen, H. T.; Demirkan, E.; Erdogdu, M. (The Journal of Sports Medicine and Physical Fitness, 2016)
AIM: In this study the Sport Experts ™ brand of hand grip dynamometer, measuring the continuity of force with the new developed load cell technology, was compared with Takei and Baseline® dynamometers, the current in use. It was tried to determine the correlation between them. In a study with provides use of clinical, orthopedic and rehabilitative purposes in the athletes and patient populations, this developed dynamometer can provide useful data by observing the continuity of force.